1984
DOI: 10.1128/iai.46.3.835-838.1984
|View full text |Cite
|
Sign up to set email alerts
|

Association of hydroxamate siderophore (aerobactin) with Escherichia coli isolated from patients with bacteremia

Abstract: Clinical isolates of Escherichia coli were examined for the presence of hydroxamate siderophore (aerobactin). The incidence of aerobactin-positive strains of E. coli from the blood was greater than the incidence of these strains isolated from other sites. The presence of aerobactin and the virulence of strains of E. coli in urinary tract infection were also examined in mice. The presence of aerobactin in the strains of E. coli correlated with virulence as measured by proportion of deaths but not with renal inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 16 publications
2
34
0
3
Order By: Relevance
“…The latter number is in the same range as reported for normal fecal E. coli isolates. The percentage of E. coli diarrheal strains which express the aerobactin receptor is similar to the aerobactin-positive E. coli isolated from extraintestinal infections [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…The latter number is in the same range as reported for normal fecal E. coli isolates. The percentage of E. coli diarrheal strains which express the aerobactin receptor is similar to the aerobactin-positive E. coli isolated from extraintestinal infections [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of E. coli the aerobactin system is most frequently found among strains from neonatal meningitis, septicaemia and urinary tract infections [13,14]. Indeed, in a particular group of strains from human pyelonephritis the frequency of aerobactin synthesis was as high as that of P-fimbriae and higher than that of haemolysin, both recognised virulence-enhancing factors in uropathogenic E. coli [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial virulence is multifactorial, and the virulence characteristics of E. coli have been studied in UTIs and bacteraemia [1][2][3]. Among the proposed virulence factors are fimbrial adhesins, haemolysin, siderophores, serum resistance and inactive serum resistance [4][5][6][7][8]. Iron compounds are known to increase the growth of bacteria, and enteric bacteria produce a catechol-type siderophore, enterobactin, and a hydroxamate-type siderophore, aerobactin, under conditions of iron starvation in vitro [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The role of siderophores was investigated in the present study with the subcutaneous route, as it was quick, easy and practical. The role of aerobactin and other virulence factors in pathogenicity has been studied previously in mice [8,18,19]. Torres et al [19] suggested that TonB was required for iron uptake by uropathogenic E. coli in a mouse model of UTI, as TonBnegative mutant isolates showed reduced virulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation